The Responses of Road Users on Safety Riding Campaign in Surabaya - Anak Agung Gde Kartika; Hera Widyastuti; Wahju Herijanto; Cahya Buana (Institute of Research and Community Outreach - Petra Christian University, 2008)
The implementation of safety riding in Surabaya in 2006 featuring some actions including canalization (kanalisasi), daytime headlamp rule, safety belt rule and the standardized helmet are viewed by some as not suitable with the existing condition. Canalization causes unfairness among road users. The canalization lane, mandatory for vehicle such as motorcycle and public transit (bus and mikrolet) tends to suffer bigger degree of saturation compared to the others. Not to mention the indication of overuse of battery and shorter bulbs life time due to the daytime headlamp rule application. Although the evaluation of the safety riding campaign covers several aspects, this paper only discuss the responses of road users to safety riding campaign especially canalization and daytime headlamp rule. The data collecting process is carried out by distributing 332 questionnaires to all road users including motorcyclists, car drivers and public transit users. The instant responses are also collected and summarized from several websites. Furthermore, the descriptive and inference statistical analysis are deployed to give the common view of response of road users as well as tabulate the summary of website-posted response. The results show that, generally most of road users support the safety riding campaign. On the contrary, most of road users agree that the daytime headlamp rule did consume more both battery and bulbs. Meanwhile, the website-posted responses varies between agree and disagree with their own reasons.